Why is Pasar KAMU a Famous Tourist Destination in North Sumatra? Study of Cultural Tourism Development Model in Denai Village, Deli Serdang, North Sumatra: Studi Model Pengembangan Wisata Budaya Di Desa Denai, - Siregar, Simon P.; Hidayat, Hidayat; Sibarani, Robert (Universitas Medan Area, 2024)
The research objectives are to identify agro-tourism and culinary tourism spots, analyze the architectural landscape, develop the The Pasar KAMU as a culinary tourism based on local wisdom and analyze community and stakeholder participation in the development of the Pasar KAMU. Data methods and analysis use qualitative data methods and analysis and data collection through observation, in-depth interviews, and literature study. Research results: (1) the spots and facilities at Pasar KAMU are adequate for nature tourism and culinary tourism activities; (2) the layout and shape of the stand for selling traditional food at The Pasar KAMU applies an ecological architectural landscape and blends with nature, optimal use of local materials and resources; (3) culinary tourism which is served in the form of traditional Javanese and Malay food, processed manually and hygienic products (4) The medium of exchange at The Pasar KAMU is very unique, using tempo which has a nominal value of IDR 5000 and IDR 10,000 (5), The Pasar KAMU is superior tourist destinations are related to the participation of residents and tourism sector stakeholders which has an impact on increasing community income.